The sociodemographic factors on food insecurity among household living in disaster-prone area in Central Java, Indonesia - Hastuti, Vivilia Niken; Afifah, Diana Nur; Sugianto, Denny Nugroho; Anjani, Gemala; Noer, Etika Ratna (Jurnal Gizi Indonesia (The Indonesian Journal of Nutrition), 2024)
Background: Demak, as a disaster-prone coastal area in Central Java, faces issues such as malnutrition and food insecurity due to the impacts of climate change. As a result of coastal disasters, vulnerable people in coastal areas often experience loss of livelihoods, limited access to nutritious food, and increased risk of malnutrition.Objective: The study aimed to analyze the association between household food security and household demographic factors in Central Java’s coastal areas.Materials and Methods: A cross-sectional study was conducted on 138 households living in the coastal area of Demak by simple random sampling. The socio-demographic characteristics were conducted by interviewing the mother/child caregiver. The degree of household food security (HFS) was obtained using the Household Food Security Survey Module (HFSSM) Questionnaire. Descriptive statistics and Chi-square were used for statistical analysis.Results: Based on HFS status, 49.3% of respondents were food secure, 26.1% were food insecure without hunger, 20.3% were food insecure with moderate hunger, and 4.3% were food insecure with severe hunger. There was significant correlation between father’s educational level, mother’s educational level, and monthly household income per month on the HFS status (p<0.05).Conclusion: Sociodemographic factors associated with household food security status were father's and mother's education and monthly household income (p<0.05). The potential negative impact of household food insecurity on the nutritional status of family members needs to be studied further, especially vulnerable age groups such as toddlers and mothers in the household.